Independensi Pengawasan Anggota Lembaga Perlindungan Saksi Dan Korban - Ndaru Satrio; Toni Toni (PROGRESIF: Jurnal Hukum, 2021)
The problem in question is the independence of supervision of LPSK members. This is related to the mechanism for forming an advisory board and an ethics board that affects the pattern of supervision of LPSK members when it is correlated with the determination of LPSK members who are suspected of committing disgraceful acts. The analytical knife used is independence. The formation of this advisory board and ethics board must go through a selection formed by the President. The reason for the formation of the advisory board and the ethics board must go through a selection mechanism by the selection committee that forms the president, so that the supervision carried out within the LPSK becomes more independent.